Innovative Approaches to Tropical Forest Management: Integrating Conservation and Utilization - Taro, Nanakorn; Kawai, Zittipong (Journal of Selvicoltura Asean, 2024)
Tropical forests, rich in biodiversity and critical to global ecological balance, face severe threats from deforestation, climate change, and unsustainable exploitation. These forests are essential for carbon sequestration, climate regulation, and the livelihoods of millions of people. Effective management that balances conservation with sustainable utilization is imperative to address these challenges. This study aims to explore and evaluate innovative approaches to tropical forest management that integrate conservation and utilization. The goal is to identify strategies that enhance biodiversity, support local communities, and contribute to global environmental objectives. The research employs a comprehensive literature review and case study analysis. It examines community-based forest management (CBFM), sustainable utilization techniques, technological innovations, and policy frameworks. Data sources include scientific journals, policy reports, and case studies from tropical regions such as the Amazon, Southeast Asia, and Central Africa. The findings highlight successful integrative strategies such as CBFM, which involves local communities in forest governance and benefit-sharing. Agroforestry and the sustainable harvest of non-timber forest products (NTFPs) are shown to enhance biodiversity and economic returns. Technological advancements like remote sensing, GIS, and drones significantly improve forest monitoring and management. Effective policy frameworks and international cooperation are critical to the success of these approaches. Integrative approaches to tropical forest management that combine conservation and sustainable utilization are vital for the resilience and productivity of these ecosystems. Engaging local communities, leveraging technology, and strengthening policies are essential to achieving sustainable outcomes. Continued research and collaboration are necessary to refine these strategies and ensure their effectiveness in diverse tropical contexts.